Verbal Analogies Computerized Adaptive Test: Comparison of Stopping Rules - Lozzia, Gabriela Susana (2020)
This study seeks to update Argentine psychometric studies. A Computerized Adaptive Test (CAT) was developed from a Verbal Analogies Item Bank (IB); it was programmed with FastTEST Pro version 2.0. A sample of 108 undergraduate students was assessed. Results were compared according to three different CAT termination criteria (fixed length of 32 items, variable length when reaching an estimation error of less than or equal to .40 and to .30). Significantly high correlations were obtained (r > .90; p < .001) between the level of trait estimated from the BI and each of the three CAT variants. Given the BI characteristics, the fixed-length of 32 items for the CAT presented the optimal balance between precision and length.